Two mixed-valent cerium oxo clusters: synthesis, structure, and self-assembly - Gao, Yuan; Zhang, Yang; Han, Zhe; Wang, Chunhui; Zhang, Lei; Qiu, Jie (Frontiers in Chemistry, 2024)
Two sets of reactions were conducted using cerium nitrate and H2O2-oxidized cerium nitrate, resulting in the formation of two distinct mixed-valent cerium oxo clusters (CeOCs) [Ce III 4Ce IV 10O14(OH)2(PhCO2)22(DMF)6] (Ce14) and [Ce III 2Ce IV 22O28(OH)8(PhCO2)30(DMF)4] (Ce24C). These two clusters exhibit different structures and Ce(III)/Ce(IV) ratios, demonstrating the critical role of cerium oxidation states and the occurrence of redox reactions in cluster formation. Ce14 is the first tetradecanuclear CeOC with a novel structure, whereas Ce24C differed in its Ce(III)/Ce(IV) ratio, protonation levels of O atoms, and ligands from previously reported 24-nuclear CeOCs. Furthermore, various techniques were employed to investigate the formation process of these two clusters. X-ray photoelectron spectra (XPS) revealed that the white precipitates formed during the preparation of Ce14 contain Ce(III) ions, while the reddish-brown precipitates formed during the preparation of Ce24C contain a mixture of Ce(III) and Ce(IV) ions. These two precipitations were individually dissolved in N,N-Dimethylformamide (DMF). The evolution of solution color and ultraviolet-visible (UV-Vis) spectra over time revealed the gradual oxidation of partial Ce(III) ions by oxygen in the solution of the white precipitation. As Ce(IV) ions increased in this solution, time-resolved small angle X-ray scattering (SAXS) data demonstrated the self-assembly of the Ce14 clusters after four days. In contrast, SAXS data and UV-Vis spectra revealed the rapid assembly of Ce24C clusters within two hours due to the initial coexistence of Ce(IV) and Ce(III) ions in the DMF solution of the reddish-brown precipitation. The continued reduction of partial Ce(IV) ions in this solution does not affect Ce24C clusters' formation and stability. Our studies expand the family of CeOCs and enhance our understanding of the effects of cerium's oxidation states on cluster formation.